Geoinformation Technologies and Spatial Analysis of Carbon Dioxide Transport through Border Line - Lesiv, M.; Bun, R. (Штучний інтелект, 2010)
Geoinformation technologies and methods of spatial analysis of emissions in the border regions have been developed and GIS based software has been created for estimating mass of carbon dioxide (CO2) emissions that goes through border line. Described mathematical models of processes of CO2 emissions in the energy sector in the border regions take into account the meteorological data. Spatial analysis of carbon dioxide transport processes has been done for Ukrainian – Polish border zone in consideration with wind rose. Описаны геоинформационные технологии и методы пространственного анализа эмиссий парниковых газов в приграничных регионах и создано программное обеспечение для численного моделирования процессов переноса диоксида углерода через границу. Предложенные математические модели процессов эмиссии углекислого газа в энергетическом секторе западных регионов Украины для вычисления перемещения атмосферных масс учитывают метеорологические условия, а именно – розу ветров. Пространственный анализ эмиссий углекислого газа был сделан для украинско-польской пограничной полосы. Описано геоінформаційні технології та методи просторового аналізу емісій парникових газів в прикордонних регіонах та створено програмний засіб для числового моделювання процесів переносу діоксиду вуглецю через лінію кордону. Запропоновані математичні моделі процесів емісії вуглекислого газу в енергетичному секторі західних регіонів України для обчислення переміщення атмосферних мас враховують метеорологічні умови, а саме – розу вітрів. Просторовий аналіз емісій вуглекислого газу зроблено для українсько-польської прикордонної смуги.